2013
DOI: 10.4161/hv.24340
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protective vaccine efficacy of the bivalent HPV vaccine against HPV31 is associated with humoral immune responses

Abstract: High HPV16 levels and avidity, and the ability to neutralize HPV31 were associated with protection against newly detected HPV31 infections, suggesting that the partial VE demonstrated for HPV31 is likely to be mediated at least in part through antibodies induced by HPV16/18 vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…7,15 For example, Cervarix Ò has shown approximately 77.1% cross-protection against HPV-31, 23 while Gardasil Ò has only shown significant efficacy against HPV-31 persistent infection. 24 The induction of low level HPV-58 neutralizing titers following Gardasil Ò administration is also in agreement with a previous report 25 but remains difficult to interpret, as this vaccine does not seem to show cross-protection against HPV-58.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 For example, Cervarix Ò has shown approximately 77.1% cross-protection against HPV-31, 23 while Gardasil Ò has only shown significant efficacy against HPV-31 persistent infection. 24 The induction of low level HPV-58 neutralizing titers following Gardasil Ò administration is also in agreement with a previous report 25 but remains difficult to interpret, as this vaccine does not seem to show cross-protection against HPV-58.…”
Section: Discussionmentioning
confidence: 99%
“…4 There are 2 licensed HPV vaccines (HPV-16/18/6/11, Gardasil Ò and HPV-16/18, Cervarix Ò ) with excellent efficacy against vaccine types and some degree of protection against HPV-16 and HPV-18 phylogenetically related non-vaccine types. [5][6][7][8] Both HPV vaccines are virus-like particles (VLPs) based on the major HPV capsid protein L1. Antigenically the vaccines are very similar but are produced in different systems and contain different adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes esquemas de vacunación no parecen alterar en gran medida la respuesta inmune general (105), dado que existe cierta evidencia de que, al menos, existe una protección parcial, después de una o dos dosis de la vacuna contra el VPH (106). A su vez, existe una buena correlación entre la protección cruzada frente a 3vHPV y los títulos de anticuerpos después de la inmunización por 2vHPV (107). La administración conjunta de vacunas contra el VPH con otras vacunas importantes, como hepatitis A, hepatitis B, vacuna meningocócica o tétanos, difteria y tosferina no ha presentado respuestas inmunes inferiores al VPH en comparación con la vacuna del VPH aislada (108).…”
Section: Según El Servicio De Medicina Preventiva Y Gestión De Calidaunclassified
“…HPV vaccine type-specific protection is assumed to be mediated by L1-neutralizing antibodies, which can be detected in the serum and cervicovaginal secretions of vaccinees (16,(19)(20)(21)(22). The role of L1-neutralizing antibodies in mediating cross-protection is less clear, although a recent study reported an association between the presence of HPV31 cross-neutralizing antibodies and a reduced risk of HPV31 infection (23). Next-generation L1 VLPbased vaccines aim to extend the breadth of coverage by incorporating an increased number of L1 VLPs (24,25).…”
mentioning
confidence: 96%